Exploring the potential of microbial inoculant to enhance common bean (Phaseolus vulgaris L:) yield via increased root nodulation and soil macro-nutrients - Sien Tigah Fortu; Aaron Suh Tening; Solange Takwi Ndzeshala; Christopher Ngosong (PLoS ONE, 2025)
Soil fertility constraints for common bean ( Phaseolus vulgaris L.) production are often resolved using chemical fertilizers, but microbial inoculants can be used as a sustainable option/complement. Microbial inoculant formulation was tested on common bean in a randomized-complete-block-design field experiment with eight treatments and four replicates. The treatments included no input(control), chemical fertilizer(NPK), poultry manure(PM), Microbial inoculants(MI), NPK + PM, NPK + MI, PM + MI, and NPK + PM + MI. Microbial inoculant treatment had the highest fertilizer replacement value (proportion of chemical fertilizer that an alternative input can substitute) relative to poultry manure(41.6%) and chemical fertilizer(26.7%). The highest bean yield(3.46 tons ha -1 ) that was observed in the NPK + PM + MI treatment was significantly ( P < 0.001) different from the microbial inoculant treatment(1.71 tons ha -1 ) and the control(1.42 tons ha -1 ). The highest 1000-grain weight (494 g) that occurred in NPK + PM + MI inoculant treatment was significantly ( P < 0.05) different from the MI(457 g), NPK(448 g), PM(436 g), and control(421 g) treatments. Effective root nodules correlated positively ( P < 0.05) with bean yield ( r = 0.77) and 1000-grain weight ( r = 0.90). Application of NPK + PM + MI had higher nodule number (9) and effectiveness than the control (2). Soil pH (6.6) was significantly ( P < 0.05) higher in NPK + PM + MI than MI + PM (6.5), control (5.5) and NPK (5.0). Soil nitrogen and available phosphorus increased significantly ( P < 0.05) in NPK + PM + MI 0.25% and 8.68 mg/kg, respectively, than the control(0.13% and 6.31 mg/kg), while higher potassium(2.80 cmol/kg) occurred in NPK than control(1.70 cmol/kg). These findings highlight the potential to explore the ability of bio-inoculant to boost root nodulation, enhance soil macro-nutrients, and modulate soil pH in bean production systems.